Effects of partial defoliation on carbon and nitrogen partitioning and photosynthetic carbon uptake by two-year-old cork oak (Quercus suber) saplings (Tree Physiology, 2004)
At the end of the growing season in late July, 20-month-old cork oak (Quercus suber L.) saplings were partially defoliated (63% of leaf area) to evaluate their ability to recover leaf area after defoliation. At 18 and 127 days after defoliation, changes in starch and nitrogen pools were determined in leaves and perennial organs, and variations in photosynthetic carbon uptake were investigated. To determine the role of stored nitrogen in regrowth after defoliation, plant nitrogen was labeled in the previous winter by enriching the nutrient solution with 15N. Plants recovered the lost leaf area in 127 days. Although there was remobilization of starch and nitrogen from leaves and perennial organs, the availability of resources for growth in the following spring was not decreased by defoliation. On the contrary, starch concentration in coarse roots was higher in defoliated saplings than in control saplings, presumably as a result of the higher net CO2 exchange rate in newly developed leaves compared with pre-existing leaves.
10.1093/treephys/24.1.83